Rural Partnerships in New England: Learning from Kids - Eva I. Kampits (Journal of Research in Rural Education, 1996)
The New England Association of Schools & Colleges (NEASC), the oldest accrediting association in the United States, established the Office of School/College Relations (OSCR) in 1990 to encourage collaborative activities that strengthen education. While the six-state region ofNew England boasts more than two hundred collaboratives, chiefly between schools and colleges, fully half were formed some 20 years ago. Rural partnerships define an even smaller number; of which only 110 are listed among more than 2,400 partnerships surveyed by the University ofSyracuse since 1986. Few, if any, are involved in systemic reform. This paper focuses on NEASC's recent undertaking of the "Rural Partnershipsfor Students' Success Project," to enhance conditions which will improve equity and access to postsecondary education. The effort to strengthen institutions' ability to meet accrediting standards reflects lessons learned from the study ofstudent aspirations and implicationsfor rural education reform.